Sensory Qualities Point to Different Structural and Functional Skin Patterns in Chronic Pruritus Patients. A Translational Explorative Study - Johanna Hidding; Konstantin Agelopoulos; Manuel P. Pereira; Heike Conrad; Hanns Hatt; Tobias Lotts; Nani Osada; Esther Pogatzki-Zahn; Martin Schmelz; Sonja Ständer (Medical Journals Sweden, 2019)
Chronic pruritus (CP) is often accompanied by paresthetic sensations like warmth, burning and stinging. The aim of this study was to analyze, whether divergent sensations are linked to structural and functional skin alterations in clinically diagnosed CP patients. Clinical responses to capsaicin, histamine, and to thermal and mechanical stimulation, intraepidermal nerve fiber density, and epidermal expression of transient receptor potential (TRP)-channels were investigated in healthy controls, and in CP patients, reporting either warmth (CP-W) or neuropathic sensations (CP-N). In CP-W, pinprick hyperalgesia and increased sensitivity to capsaicin were aligned with increased epidermal TRPV1 expression, while smaller histamine axon reflex erythema matched with significantly reduced intraepidermal nerve fiber density. CP-N showed earlier onset of sensations after capsaicin stimulation, significantly increased warmth detection threshold, and higher epidermal expression of TRPV4 compared to healthy controls. The present study contributes to the neurobiological understanding of the divergence of sensory sensations in CP, indicating new treatment targets.